2006
DOI: 10.1007/s11095-006-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam and Gamma Radiolysis of Solid-State Metoclopramide

Abstract: Solid-state metoclopramide is radioresistant from a chemical point of view and therefore could be a suitable candidate for radiosterilization studies by either gamma rays or high-energy electrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The water molecules needed for these two reactions (formation of the radiodegradation products) most probably come from the air atmosphere of the reaction or from the compound studied, as its moisture content is of about 0.5%. The latter interpretation is shared by the majority of researchers 21 and is supported by the fact that the ionizing radiation has greater penetrating power through the solid body than light, which can initiate reactions with the air components of water contained in the illuminated compound. 30 As follows from our results, none of the radiolysis products is colorful so the coloring of the SMX irradiated in solid state most probably comes from trapping of free radicals in the crystal lattice defects, as indicated by the changes in the XRD patterns.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The water molecules needed for these two reactions (formation of the radiodegradation products) most probably come from the air atmosphere of the reaction or from the compound studied, as its moisture content is of about 0.5%. The latter interpretation is shared by the majority of researchers 21 and is supported by the fact that the ionizing radiation has greater penetrating power through the solid body than light, which can initiate reactions with the air components of water contained in the illuminated compound. 30 As follows from our results, none of the radiolysis products is colorful so the coloring of the SMX irradiated in solid state most probably comes from trapping of free radicals in the crystal lattice defects, as indicated by the changes in the XRD patterns.…”
Section: Resultsmentioning
confidence: 97%
“…[17][18][19] According to some authors, the influence of the two types of radiation on degradation of drugs is close to each other or is the same. 20,21 As gamma irradiation dose rate is low (~10 kGy/h) relative to that of e-beam (~10 kGy/s), the time of irradiation for gamma sterilization must be longer, which implies prolonged exposure to ozone formed from oxygen in the air and increased probability of free radicals reacting with diffusing oxygen, which would initiate a series of destructive reactions (e.g. oxidation) and would accelerate degradation of irradiated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs have shown a gamut of changes in the physical properties (change in colour, change in crystallisation degree and change in chirality) and chemical properties (oxidation, cleavage of chemical bonds, dehydrogenation, formation of free radicals) after irradiation with a minimum dose. The changes were often directional and intensified with increasing dose of irradiation [10,13,[20][21][22][23][24][25][26][27][28]. For many irradiated drugs also a shift of the melting point was observed towards lower temperatures which was related to the appearance of Magnetic field/mT EPR signal intensity/a.u.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that bond breakage between the carboxy and nitrogen of the amide group had occurred. Maquille et al reached a different conclusion after applying different doses of g-radiation and high-energy electrons to investigate the influence of dose rate on radiolysis of MCP HCl H 2 O [112]. These authors found that there was no significant difference between g-ray and e-beam irradiations of MCP HCL H 2 O.…”
Section: Solid-state Radiolysismentioning
confidence: 99%